Dynamics of Macronutrients in the San Jorge Gulf During Spring and Summer - Torres, Américo Iadran (2018)
Following designation of San Jorge Gulf (SJG) as a priority for marine conservation by the Argentine scientific community, it was included in the “Pampa Azul” government initiative. As a contribution to this initiative, we analyzed macronutrient distribution and its relationship to the stratification and primary producer biomass in the water column during austral summer 2014 and spring 2016. In addition, we determined dissolved oxygen, chlorophyll concentrations, and pH. During both seasons in the central and northern gulf, strong stratification separated nutrient-poor, oxygenated surface waters from nutrient-rich, less-oxygenated deep waters. Thermal stratification was correlated to nutrient concentrations. Oxygen decreased up to 60% in bottom waters, although hypoxic conditions were not found. Nitrate limited primary production in surface waters. A tidal front near the gulf’s mouth in the south and wind-forced upwelling in the southwestern coastal zone naturally fertilized the waters. Although there is no information on the precise amount of nutrients each source contributes to the SJG, a shortcut in the path toward resource conservation could be directed through the processes associated with water column stratification because it determines the availability of surface nutrients to primary producers.